2012
DOI: 10.1186/1471-2334-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Soluble RAGE as a severity marker in community acquired pneumonia associated sepsis

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is considered the most important cause of death from infectious disease in developed countries. Severity assessment scores partially address the difficulties in identifying high-risk patients. A lack of specific and valid pathophysiologic severity markers affect early and effective sepsis therapy. HMGB-1, sRAGE and RAGE have been involved in sepsis and their potential as severity markers has been proposed. The aim of this study was to evaluate HMGB-1, RAGE and sRAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 39 publications
3
34
0
2
Order By: Relevance
“…sRAGE levels are elevated and suggested to be a marker of outcome in patients with sepsis [29], pneumonia [30] and acute lung injury [31]. In this study, we were unable to detect sRAGE in plasma, which is in accordance with an earlier study measuring circulating sRAGE levels in diabetic mice [32].…”
Section: Discussionsupporting
confidence: 69%
“…sRAGE levels are elevated and suggested to be a marker of outcome in patients with sepsis [29], pneumonia [30] and acute lung injury [31]. In this study, we were unable to detect sRAGE in plasma, which is in accordance with an earlier study measuring circulating sRAGE levels in diabetic mice [32].…”
Section: Discussionsupporting
confidence: 69%
“…Its utility as a marker of ARDS in humans, however, is questionable and data have been very mixed. Some studies have shown an association between plasma sRAGE levels and ARDS development in mixed ICU patients [17, 36,86] and trauma patients [87], but several robust studies have not shown any association [7 & , 10,11] and it is likely that sRAGE is a marker of illness severity rather than ARDS.…”
Section: The Epithelial Markersmentioning
confidence: 98%
“…For example, it is possible that in general, endothelial cells are the major producers of soluble RAGEs but that in diabetes, peripheral blood monocytes and lymphocytes may also contribute substantially to soluble RAGE production. In this context, in subjects with sepsis, a dramatic form of disease manifestation with heightened inflammatory linked to hemodynamic abnormalities, sRAGE levels in plasma were found to be significantly higher than in control subjects [44]. Hence, we might speculate, is diabetes somewhere in the middle?…”
Section: Soluble Rages: High or Low – Confounding Factors?mentioning
confidence: 99%